Oncologic and Operative Outcomes of Robotic Staging Surgery Using Low Pelvic Port Placement in High-Risk Endometrial Cancer - Jeeyeon Kim; Jiheum Paek (Current Oncology)
Upper para-aortic lymph node dissection (PALND) is one of the most challenging gynecologic robotic procedures. This study aimed to evaluate the oncologic and operative outcomes of robotic staging surgery, including upper PALND, using low pelvic port placement (LP3) in 22 patients with high-risk endometrial cancer. High-risk was defined as patients who showed deep myometrial invasion with grade III, cervical involvement, or high-risk histology. The mean patient age and body mass index were 58 years and 24 kg/m2. The mean operative time was 263 min. The mean number of total LNs and upper PALNs obtained was 31 and 10. Two patients received lymphangiography to reduce the amount of drained lymphatic fluid after surgery. The recurrence rate was 13.6% (3/22). There were two LN recurrences and one at the peritoneum in the intra-abdominal cavity. Robotic staging surgery using LP3 was feasible for performing PALND as well as procedures in the pelvic cavity simultaneously. It provides important techniques for performing optimal surgical procedures when surgeons decide to perform comprehensive PALND in instances of isolated recurrence or unexpected LN enlargement as well as high-risk endometrial cancer. Consequently, surgeons can achieve surgical consistency and reproducibility for PALND, leading to improved operative and survival outcomes in high-risk endometrial cancer.